Insulin resistance and arterial stiffness: impact of gestational diabetes on pulse wave velocity - Seck, Aissatou; Agne, Fatou Diallo; Fall, Abibatou Sall; Sar, Fatou Binetou; Ouedraogo, Valentin; Mbengue, Arame; Hallab, Magid; Ba, Abdoulaye; Samb, Abdoulaye (International Journal of Research in Medical Sciences, 2018)
Background: Gestational diabetes is an intolerance of glucose with the first appearance during the pregnancy. This hyperglycaemia status, because of the pre-existing insulin-resistance, constitute a favourable land of arterial stiffness. The aim of this study is to determine the impact of non obese gestational diabetes on arterial stiffness by measuring the pulse wave velocity (PWV). Methods: We recruited 60 pregnant women aged from 20 to 35 years old. They were between twentieth four and thirtieth five weeks of gestational age. Subjects were divided into two groups: the first group (G1), considered as control group, included 25 normoglycemic pregnant subjects without any history of illness or risk factors of gestational diabetes; the second group (G2) included 35 women with Gestational Diabetes Mellitus (GDM). All pregnant women had not history of smoking, were not taking decoction or medicine, which could disturb pregnancy evolution. Anthropo-physiological and biochemical parameters studied, were: age, body mass index (BMI), blood pressure (BP), triglyceride, cholesterol and HOMA-IR index. The PWV between finger and toe (PWVft) was measured by pOpmètre®. Results: The two groups are matched by age (G1:28±4ans; G2:29±3ans) and BMI (G1:25.6±1.27; G2:26.9±1.3). Blood pressure (BP) values are in normal interval (systolic BP: [110-132mmHg]; diastolic BP: [63-87mmHg]; mean BP: [79-103mmHg]). Total cholesterol (G1:0.95±0.08;G2:2.4±0.7; p˂0.0001), HDL cholesterol (G1:0.44±0.02; G2:0.76±0.2; p˂0.0001, LDL cholesterol (G1:0.40±0.05; G2:1.3±0.5; p˂0.0001), triglyceride (G1:0.57±0.45; G2:1.6±0.4;p˂0.0001), HOMA.IR (G1:1.31±1.05; G2:7.4±1.07; p˂0.01), PWVft (G1:5.99±1.23; G2:10.3±1.9; p˂0.0001) are significantly higher in diabetic group. PWVft is positively correlate to HOMA-IR index, total cholesterol, LDL cholesterol and triglycerides (r=0.3348, p=0.032; r=0.5275, p˂0.0001; r=0.4855,p˂0.0001; r=0.5581, p˂0.0001respectively). Conclusions: Gestational diabetes might induce an increase of pulse wave velocity expressing increment of arterial stiffness. This last constitute an early underlying cardiovascular risk.